Wearable Wireless Tactile Display for Virtual Interactions with Soft Bodies - Frediani, Gabriele; Mazzei, Daniele; De Rossi, Danilo Emilio; Carpi, Federico (Frontiers in Bioengineering and Biotechnology, 2014)
We describe here a wearable, wireless, compact and lightweight tactile display, able to mechanically stimulate the fingertip of users, so as to simulate contact with soft bodies in virtual environments. The device was based on dielectric elastomer actuators, as high-performance electromechanically active polymers. The actuator was arranged at the user’s fingertip, integrated within a plastic case, which also hosted a compact high-voltage circuitry. A custom-made wireless control unit was arranged on the forearm and connected to the display via low-voltage leads. We present the structure of the device and a characterization of it, in terms of electromechanical response and stress relaxation. Furthermore, we present results of a psychophysical test aimed at assessing the ability of the system to generate different levels of force that can be perceived by users.